The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2042018819842971
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass is associated with the risk of all-cause mortality in patients with type 2 diabetes mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) have an increased risk of muscle mass reduction. However, the association between muscle mass and mortality in T2DM remains unknown. Methods: This was a historical cohort study with the endpoint of all-cause mortality. This study included 163 Japanese men and 141 postmenopausal women with T2DM whose body compositions were evaluated using dual-energy X-ray absorptiometry. Low muscle mass was defined as a skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 19 publications
(30 reference statements)
3
29
0
3
Order By: Relevance
“…Protein synthesis in skeletal muscle is decreased by type 1 DM (T1DM) due to loss of insulin signaling, and protein degradation is enhanced with myostatin-mediated autophagy in type 2 DM (T2DM) ( Sala and Zorzano, 2015 ). Particularly, an age-adjusted study reported that muscle wasting is an independent risk for all-cause mortality in patients with T2DM ( Miyake et al, 2019 ). Prevention of DM-associated muscle loss is an important subject but there is no efficacious drugs, because it is still a complicated pathology and underlying mechanism has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Protein synthesis in skeletal muscle is decreased by type 1 DM (T1DM) due to loss of insulin signaling, and protein degradation is enhanced with myostatin-mediated autophagy in type 2 DM (T2DM) ( Sala and Zorzano, 2015 ). Particularly, an age-adjusted study reported that muscle wasting is an independent risk for all-cause mortality in patients with T2DM ( Miyake et al, 2019 ). Prevention of DM-associated muscle loss is an important subject but there is no efficacious drugs, because it is still a complicated pathology and underlying mechanism has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Aging and obesity are major risk factors in diabetes mellitus (DM), and the number of patients with DM is increasing worldwide. Muscle wasting is associated with the risk of mortality in patients with DM (Miyake et al, 2019). Therefore, the prevention and treatment of DM-associated sarcopenic obesity is important for public health (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle is a major organ for glucose metabolism [ 9 ]; therefore, muscle is an important target for treatment of patients with T2D. It has been reported that muscle mass loss is associated with low quality of life [ 28 ], cardiovascular disease [ 29 , 30 ], and mortality [ 31 ]. Previous studies revealed that muscle mass of patients with T2D is unchanged or slightly decreased in the natural course [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%